1995
DOI: 10.1042/bj3100171
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of tissue-type plasminogen activator gene expression by sodium butyrate and trichostatin A in human endothelial cells involves histone acetylation

Abstract: We have previously shown that the pleiotropic agent sodium butyrate strongly stimulates tissue-type plasminogen activator (t-PA) expression in human umbilical vein endothelial cells (HUVEC). Here we provide the following evidence that the butyrate-induced t-PA expression in HUVEC involves histone H4 acetylation. (1) t-PA induction by butyrate occurs at the transcriptional level and does not require new protein synthesis, indicating a direct effect. (2) t-PA induction by butyrate can be fully mimicked by a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 31 publications
6
61
0
Order By: Relevance
“…Histone acetylation influences the higher order structure of chromatin, resulting in a chromatin conformation that is more accessible to transcription factors and leading to enhanced transcription of some genes (17). As part of our effort to optimize conditions for evaluating VR1 pharmacology, we have found that butyrate can influence the function of VR1.…”
Section: Resultsmentioning
confidence: 98%
“…Histone acetylation influences the higher order structure of chromatin, resulting in a chromatin conformation that is more accessible to transcription factors and leading to enhanced transcription of some genes (17). As part of our effort to optimize conditions for evaluating VR1 pharmacology, we have found that butyrate can influence the function of VR1.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, a variety of proteins can be up-regulated by TSA. The prominent examples include p21 WAF1/CIP1 (32,33), gelsolin (35), cytokeratin A (endoA) (39), Stra13 (40), and plasminogen activator (41). p21 WAF1/CIP1 is an inhibitor of cyclin-dependent kinase, and Stra13 is a transcriptional repressor of the c-myc gene.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, histone H4 in heterochromatin regions was less acetylated at lysines 5 and 8 but hyperacetylated at lysine 12 (67). In contrast to all other chromosomes, the inactive mammalian X chromosome is largely unlabelled by specific antibodies directed against the acetylated form of lysines 5,8,12, and 16 at histone H4 (27). Immunoprecipitation of chromatin fragments from human HL-60 cells with similar antibodies confirmed that the heterochromatin contains underacetylated forms of H4, although the acetylation of histone H4 was not correlated with transcriptional activity (47).…”
mentioning
confidence: 98%
“…Another important step toward the understanding of the role of histone acetylation was the identification of specific inhibitors of histone deacetylases (12; for a review, see reference 77). Trichostatin A, a fungistatic antibiotic, has been shown to induce differentiation in erythroleukemia cells (78), to block the development of Xenopus and starfish embryos (2), to induce the expression of different genes (5,20,25,43), and to arrest normal fibroblasts in the G 1 or G 2 phase of the cell cycle (76). Furthermore, trichostatin A and trapoxin, another specific inhibitor of histone deacetylases, also have the potential to revert the phenotype of oncogene-transformed fibroblasts (17,62,75).…”
mentioning
confidence: 99%